A Tactical Chaos based PWM Technique for Distortion Restraint and Power Spectrum Shaping in Induction Motor Drives - V. Mohan; N. Stalin; S. Jeevananthan (Institute of Advanced Engineering and Science, 2015)
The pulse width modulated voltage source inverters (PWM-VSI) dominate in the modern industrial environment. The conventional PWM methods are designed to have higher fundamental voltage, easy filtering and reduced total harmonic distortion (THD). There are number of clustered harmonics around the multiples of switching frequency in the output of conventional sinusoidal pulse width modulation (SPWM) and space vector pulse width modulation (SVPWM) inverters. This is due to their fixed switching frequency while the variable switching frequency makes the filtering very complex. Random carrier PWM (RCPWM) methods are the host of PWM methods, which use randomized carrier frequency and result in a harmonic profile with well distributed harmonic power (no harmonic possesses significant magnitude and hence no filtering is required). This paper proposes a chaos-based PWM (CPWM) strategy, which utilizes a chaotically changing switching frequency to spread the harmonics continuously to a wideband and to reduce the peak harmonics to a great extent. This can be an effective way to suppress the current harmonics and torque ripple in induction motor drives. The proposed CPWM scheme is simulated using MATLAB / SIMULINK software and implemented in three phase voltage source inverter (VSI) using field programmable gate array (FPGA).